Filsafat sains dalam perspektif pemikiran Islam - Hardiansyah, Nur (Maliki Interdisciplinary Journal, 2024)
This research examines the philosophical dimensions of the Islamic scientific framework as well as the interdependence of humans, nature, and God within Islamic science, along with its eschatological perspectives. The qualitative-descriptive method is employed using primary sources of writings by scholars on modern Western science and Islamic science. Findings indicate that the Islamic scientific framework refers to both religious and scientific structures, combining basic assumptions and methodologies of science with Islamic principles such as Tauhid. The interdependence among humans, nature, and God is reflected in the objective of Islamic science to demonstrate the unity of all existence. Eschatology in scientific theory highlights the source and purpose of intellectual knowledge, emphasizing that only science based on Tauhid values can bring happiness. In conclusion, Islamic science reflects the main principles of the Islamic worldview and provides a foundation for a holistic understanding of cosmic reality.